Biallelic human ITCH variants causing a multisystem disease with dysmorphic features: A second report. Issue 7 (15th May 2019) - Brittain, Helen K.; Feary, Johanna; Rosenthal, Mark; Spoudeas, Helen; ,; Wilson, Louise C.
Abstract: We report a 23 year old female with biallelic truncating variants in the ITCH (Itchy E3 Ubiquitin protein ligase, mouse homolog of; OMIM60649) gene associated with marked short stature, severe early onset chronic lung disease resembling asthma, dysmorphic facial features, and symmetrical camptodactyly of the fingers but normal intellect. The condition has only been reported once previously (Lohr et al., American Journal of Human Genetics, 2010, 86, 447–453) in 10 children from an Old Order Amish family found to have a homozygous frameshift truncating variant in association with failure to thrive, chronic lung disease, motor and cognitive delay, and variable autoimmune diseases including autoimmune hepatitis, enteropathy, hypothyroidism, and diabetes. The condition is listed in OMIM as Autoimmune disease, Multisystem with Facial Dysmorphism (OMIM613385). The clinical course as well as the dysmorphic facial and limb features overlap closely with our patient. We believe the triad of marked syndromic short stature, chronic lung disease, and dysmorphism (with or without cognitive impairment and wider autoimmune involvement) is distinctive.